Influence of manure concentration as inoculum in anaerobic digestion of vinasse - Carlos Eduardo de Farias Silva; Ana Karla de Souza Abud (Acta Scientiarum. Biological Sciences, 2017)
Vinasse, main residue of the sugarcane industry, has high pollutant content, being subjected to the use in biogas production due to the high content of organic matter non-toxic to microbial action. For a consolidated process, it is necessary to study parameters that influence the process, in which the amount of inoculum is one of the major factors in the biological process of biogas production. This study investigated the influence of the amount of manure as inoculum (0.5 to 5.5%) during the biodigestion process, evaluating variables such as chemical oxygen demand (COD), pH, biogas production, methane concentration, total solids and total phosphorus and nitrogen contents, as well as microbiological analysis in the sludge remaining in the digester. Biodigestion occurred normally, with hydraulic retention time (HRT) of 20 days, with an acidogenic phase, subsequent stabilization of pH and biogas production. The vinasse had COD and total solids reduced during biodigestion by around 67 and 40%, respectively. Biogas production was increased after the fifth day. Among the three studied conditions, there was no significant increase in efficiency of inoculum use and it can be used the lowest amount, 0.5 % (m v-1).